Economic Conditions of the Migrant Workers in Kerala: A Study in the Trivandrum District - Dilip Saikia (Journal of Indian Research A Quarterly Journal of Multidisciplinary Research, 2014)
In recent years, Kerala has been experiencing a large influx of migrant workers from different parts of India. Higher wages, large employment opportunities and shortages of local labourers make Kerala a lucrative job market for workers from outside the State. The purpose of this paper is to examine the characteristics and eco- nomic condition of the migrant workers in Kerala. Based on data from a sample survey of 166 migrant work- ers, carried out during September-October, 2008 in the Trivandrum district of Kerala, this paper analyses the migrant’s demographic and household details, reasons for migration, sources of information, living conditions, occupational pattern, wage and income, consumption and savings, and remittances, etc.